0.5(4x+7)=0.6-(x-3)

Simple and best practice solution for 0.5(4x+7)=0.6-(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.5(4x+7)=0.6-(x-3) equation:


Simplifying
0.5(4x + 7) = 0.6 + -1(x + -3)

Reorder the terms:
0.5(7 + 4x) = 0.6 + -1(x + -3)
(7 * 0.5 + 4x * 0.5) = 0.6 + -1(x + -3)
(3.5 + 2x) = 0.6 + -1(x + -3)

Reorder the terms:
3.5 + 2x = 0.6 + -1(-3 + x)
3.5 + 2x = 0.6 + (-3 * -1 + x * -1)
3.5 + 2x = 0.6 + (3 + -1x)

Combine like terms: 0.6 + 3 = 3.6
3.5 + 2x = 3.6 + -1x

Solving
3.5 + 2x = 3.6 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
3.5 + 2x + x = 3.6 + -1x + x

Combine like terms: 2x + x = 3x
3.5 + 3x = 3.6 + -1x + x

Combine like terms: -1x + x = 0
3.5 + 3x = 3.6 + 0
3.5 + 3x = 3.6

Add '-3.5' to each side of the equation.
3.5 + -3.5 + 3x = 3.6 + -3.5

Combine like terms: 3.5 + -3.5 = 0.0
0.0 + 3x = 3.6 + -3.5
3x = 3.6 + -3.5

Combine like terms: 3.6 + -3.5 = 0.1
3x = 0.1

Divide each side by '3'.
x = 0.03333333333

Simplifying
x = 0.03333333333

See similar equations:

| 4.3x+25.8=64.5-8.6x | | 21a=7 | | 1/3x+2+1/2x-3=90 | | V=567 | | 3(x-4)-12+2x-9= | | 4.84x=2x | | (-3x-4)-(-2x-1)=6 | | 4(3x-5)+6=x | | 5g+14g+3= | | 4m-2=5m+7 | | 30x^2-85x+60=0 | | -2(5+6k)+16=-90 | | A^3-7a^2+6a-10= | | 4a+11-1a=2 | | 6x-4+2x-2=90 | | 42=7f | | 1300.4624=2*3.14*38.44+2*3.14*6.2*h | | -3(-10+6x)=30 | | x+13+2x+17=180 | | 1300.46=2*3.14*38.44+2*3.14*6.2h | | 80=-16t^2+35t+12 | | 6x=40+x | | 1300.46=2*3.14*38.44+2*3.14*6.2 | | -6(3+2x)=-8-2x | | y=5x-3+5x+2 | | 5(7+2x)=x-13+5x | | 0.4(x+70)+0.2x=6 | | D^2-36d+324=0 | | s=10p | | 8(7-m)=-24 | | 1300.46=2*3.14r^2+2*3.14*6.2 | | y=100+x+(7-x) |

Equations solver categories